'She Doesn't Need Muṭiyēṯṯu' There': The Interplay of Divine Mood, Taste and Dramatic Offerings in South Indian Folk Hinduism. (10th May 2018) - Pasty-Abdul Wahid, Marianne
Abstract : The selection of Bhadrakāḷi shrines of central Kerala (South India) in which the ritual drama muṭiyēṯṯu' is conducted as an offering is restricted by religious considerations surrounding the personality of the goddess: performances can only be safely and efficiently given in shrines housing a deity who is in the right mood and has the appropriate nature for being able to be pleased by them and derive benefits from them. Drawing from data primarily gathered in the context of muṭiyēṯṯu', this article highlights the role played by dramatic offerings in the management of a deity's temper. By discussing issues pertaining to the fields of both performance anthropology and religious studies, it sheds some light on the popular conceptualization of the Hindu goddess, the logic behind the composition of her worship, especially in terms of performing arts, as well as the active power assigned to drama within the popular Hindu context.